Household forming inflation expectations: Why do they 'overreact'? - Joshy Easaw (Cardiff University, Cardiff Business School, 2015)
The purpose of the present paper is to provide a simple model which explains how households (or non-experts) form their inflation forecasts. The paper contributes to the existing literature and the understanding of how inflation expectations are formed in two ways. Firstly, we present an integrated model of how non-experts form their inflation expectations. The paper initially outlines how professionals form inflation forecast. Subsequently, the model presents the non-expert's expectations formation incorporating the dynamics of the professional's forecast. Secondly, we explain the prevalent phenomena where non-experts tend to overreact, or overshoot, initially as they revise their inflation forecast.
Keywords: E3; E4; E5; 330; Inflation Expectations Formation; Information Rigidities; Overreaction